Beyond filters the political economy of pandemic phenomenon Filipino TikTokers - Pineda, Jose Mari R.
This thesis delves into the phenomenon of Filipino TikTokers during the COVID- 19 pandemic, situated within the context of the Philippines' remarkable digital landscape. This explores how users navigate and negotiate their online identities, influencing, and entrepreneurial pursuits amidst the pandemic. By examining the intricacies of digital labor, online commodification, and the performative nature of TikTok fame, this research uncovers the ways in which Filipino TikTokers have become significant cultural and economic forces, shaping the contours of online discourse, consumerism, and identity formation. Through a critical media studies framework, this research provides insight into the power dynamics, cultural politics, and economic structures that underpin the rise of Filipino TikTokers, ultimately contributing to a deeper understanding of the digital mediated experiences of the Filipino youth during the pandemic.